Influence of processing conditions on the physicochemical properties and shelf-life of spray-dried palm sugar (Arenga pinnata) powder - Lasekan, Olasegun (Taylor & Francis, 2014)
The influence of spray-drying conditions on some physicochemical properties of palm-sugar powder ( Arenga pinnata ) was studied. Twenty tests were carried out according to a central composite design. Independent variables were: inlet temperature (150–190°C), feed flow rate (9–21 g/min), and maltodextrin concentration (14–25%). Process yield, hygroscopicity, and outlet temperature were analyzed as responses. Results revealed that increasing inlet temperature resulted in higher process yield and outlet temperature and a lower hygroscopicity. Similarly, higher inlet temperature led to lower moisture content, dissolution rate, and total phenolic content of the powder. Conversely, the feed flow rate negatively influenced process yield and hygroscopicity, and positively influenced moisture content. Moreover, maltodextrin exhibited negative influence on process yield and hygroscopicity, respectively. Moreover, storage (30°C, six months) led to noticeable losses in flowability and wettability. Powder morphology was also influenced by the inlet temperature. Lower inlet temperature resulted in particles with shrivelled surfaces while higher temperature produced a greater number of larger particles with smooth surface